1985
DOI: 10.1002/actp.1985.010361213
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymerization of cotton fabric with different vinyl monomers using ferrous cellulose thiocarbonate hydrogen peroxide redox system

Abstract: The effects of hydrogen peroxide concentration, ferrous ion concentration, polymerization temperature and other factors on the graft polymerization of methacrylic acid and other vinyl monomers onto cotton using the redox system ferrous cellulose thiocarbonatehydrogen peroxide were investigated. Die Pfropfcopolymerisation von Baumwollgewebe mit Vinylmonomeren unter Verwendung des Redoxsystems Eisencellulosethiocarbonat-WasserstoffperoxidDer EinfluB der Wasserstoffperoxidkonzentration, der Few-Konzentration, der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Cellulose macroradicals generated by redox initiation systems are immobile, and for grafting, the monomer should be in the vicinity of the cellulose. The higher monomer molecule near the immobile cellulose macroradical in the polymerization medium acts in favor of molecular collision, enhancing polymerization in general or homopolymer formation in particular 10, 11. The reduced graft yield percentage beyond a certain level suggested that the rate of homopolymer formation prevailed over graft formation at higher monomer concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose macroradicals generated by redox initiation systems are immobile, and for grafting, the monomer should be in the vicinity of the cellulose. The higher monomer molecule near the immobile cellulose macroradical in the polymerization medium acts in favor of molecular collision, enhancing polymerization in general or homopolymer formation in particular 10, 11. The reduced graft yield percentage beyond a certain level suggested that the rate of homopolymer formation prevailed over graft formation at higher monomer concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…To improve interactions between AgNPs and fabric constituents, the use of binders was proposed during the treatment procedure. [27] The cotton fabrics were immersed in AgNP solution with binder (printo ® FX based on acrylate) solution and repeated several times. The treated fabrics were then squeezed to 100% wet pick up at a constant pressure, dried at 70 C for 3 min, and followed by curing at 150 C for 2 min before use.…”
Section: Solution-immersionmentioning
confidence: 99%
“…It was particularly broad in the case of the latter. El-Rafie et al 25 recently studied the influence of hydrazine hydrate, sodium sulfite, sodium hydrosulfite, thiourea dioxide, and sodium sulfite on the reaction initiated by the xanthated method. Among all these additives only hydrazine hydrate increased conversion (only 10% at hydrazine concentration 8 X mol/L).…”
Section: Influence Of Additivesmentioning
confidence: 98%